Exploring social media determinants in fostering pro-environmental behavior: insights from social impact theory and the theory of planned behavior - Liao, Chi-Horng (Frontiers in Psychology, 2024)
This study investigates the impact of social media on pro-environmental behavior (PEB) through the lens of the Theory of Planned Behavior (TPB) and Social Impact Theory. By employing both Variance-Based Structural Equation Modeling (VBSEM) and Artificial Neural Networks (ANN), the research aims to elucidate the role of social media in shaping Environmental Attitude (EA) and Subjective Norms (SN), and how these factors contribute to Behavioral Intentions (BI) that ultimately influence PEB. Additionally, it examines the moderating effect of Perceived Behavioral Control (PBC) on the relationship between BI and PEB. The analysis is based on data collected from two distinct samples: 1200 participants from Taiwan for the Structural Equation Modelling (SEM) analysis and 602 respondents for the ANN study. The dual methodological approach integrates SEM to explore causal relationships and ANN to enhance predictive accuracy. The SEM findings reveal that social media significantly affects both EA and SN, with the exception of Social Networking Site Involvement (SNSI), which does not significantly impact EA. The study also demonstrates that BI mediates the relationship between EA and PEB. However, BI does not mediate the SN-PEB relationship, and the link between SN and BI is found to be non-significant. Moreover, empirical evidence suggests that PBC moderates the BI-PEB relationship, with a stronger influence observed under higher levels of PBC and a weaker influence under lower levels. These results underscore the complex dynamics between social media factors and pro-environmental behavior. The study concludes with a discussion on the implications of these findings, the limitations encountered, and potential avenues for future research.